Implementation of Card Scenarios in Group Counseling as a Strategy for Reconstructing Teenagers’ Digital Ethics - Zahroini, Sukma Nuri; Thohir, Mohamad (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The rise of immoral behavior carried out through social media by teenagers has become a serious problem that requires appropriate handling, especially in the school environment. At MTs Negeri Gresik, cases of immoral behavior involving the misuse of social media by students were found, which impacted the development of students’ character and morals. This study aims to describe the application of the card scenario technique in group counseling as an effort to reconstruct adolescent ethics in using social media. The method used in this study is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the use of card scenarios in group counseling can facilitate students in recognizing moral values, increase self-awareness of the impact of deviant behavior, and encourage more responsible behavior in the use of social media. Thus, this technique is effective as an educational medium in the contextual and participatory counseling process.